Altruistic and egoistic behaviors in interpersonal interactions - Nowacka, Agnieszka; Smuczyński, Wojciech; Woźniak-Dąbrowska, Kamila; Lewko, Dawid (Journal of Education, Health and Sport, 2021)
Introduction. Utopian or destructive society? Is it better to be an egoist or an altruist in a group and which factors does it depend on? Aim. Difficulty in making an unambiguous assessment of social interactions was the reason for conducting a few studies which aimed at identifying factors shaping altruistic and selfish behaviors. Due to the scope of the studies, percentage results relate only to selected social communities. Materials and methods. The first study aimed at evaluating altruistic behaviors of an individual and of a group and was focused on an analysis of interpersonal interactions between a person who needed help (not calling for it) and a bystander observing the incident. The second experiment evaluated psychologization of confidence and focused on the assessment of interpersonal relations of two participants. The last, third study aimed at evaluating altruistic attitude towards various social relations. Results. Conducted studies show that there are a lot of factors which determine conscious (financial benefits, empathy) and unconscious (difficulty in interpreting the incident, inadequate intervention, unwillingness to feel responsible for own behavior) development of altruistic and egoistic behaviors in interpersonal interactions.